A pilot randomized controlled trial of a tailored smoking cessation program for people living with HIV in the Washington, D.C. metropolitan area - Kierstead, Elexis C. (BMC Res Notes, 2021)
OBJECTIVE: Morbidity and mortality from smoking-related diseases among people living with HIV (PLWH) in the U.S. surpasses that due to HIV itself. Conventional smoking cessation treatments have not demonstrated strong efficacy among PLWH. We conducted a pilot randomized controlled trial (RCT) to evaluate a tailored smoking cessation intervention based on the minority stress model. We compared standard of care counseling (SOC) to a tailored intervention (TI) including one face-to-face counseling session incorporating cognitive behavioral therapy to build resilience, and 30 days of 2-way text messaging. RESULTS: The primary outcome was smoking cessation. Secondary outcomes included cigarettes per day (CPD), exhaled carbon monoxide (CO), and cessation self-efficacy. A total of 25 participants were enrolled (TI:11, SOC:14), and 2 were lost to follow-up. There were no significant differences in quit rates between study groups. However, there was a significantly greater decrease in CPD in the TI versus SOC (13.5 vs. 0.0, p-value:0.036). Additionally, self-efficacy increased in both groups (TI p-value:0.012, SOC p-value:0.049) and CO decreased in both groups (TI p-value: < 0.001, SOC p-value:0.049). This intervention shows promise to support smoking cessation among PLWH. A larger study is needed to fully evaluate the efficacy of this approach. Clinical trial: Trial Registration: Retrospectively registered (10/20/2020) NCT04594109.